Meta‐Analisis : Gender Dan Depresi Pada Remaja - Nefi Darmayanti (Faculty of Psychology, Universitas Gadjah Mada, 2008)
The purpose of this meta‐analysis study is to evaluate primary studies that studied gender differences in adolescents depression. Articles collected from popular journal (e.g. journal of research, journal of youth adolescent, American journal of community psychology, journal of adolescence and psychology, journal of adolescence and journal of abnormal child psychology). Twenty three articles were found, but only fourteen articles were relevant. After final evaluation, only twelve articles with fourteen studies could be analyzed. Fourteen (14) studies involving 5206 subjects examined gender differences in adolescents depression